Disaster preparedness response and recovery of selected families in Balanga City, Bataan - Estrella, Ric Ernest C.; Gabriel, Florenda S. (Quezon City College of Home Economics, University of the Philippines Diliman, 2020)
This study aims to describe the family disaster preparedness, response and recovery plan of selected families in Brgy. Pto. Rivas Ibaba, Balanga City, Bataan in the aras of shelter, food, finance and protection of life. Also, to determine the level of disaster preparedness, response and recovery practices. Fifteen families under low- and middle-income level living along the coastline of the city participated in the study. The research instrument used was questions originally made by the researcher written in Filipino and the qualitative data gathered from the interview were analyzed to determine family’s disaster plan. Result shows that in general, respondents were all prepared during disaster. They are efficient in executing and following the disaster plans and shows a relatively fast recovery pace. In addition, families were able to survive with their own endeavors and with the help of the local government.
Thesis (Bachelor of Science in Home Economics)--University of the Philippines Diliman
Bibliography : pages 37-40.
Keywords: Emergency management -- Philippines -- Balanga City (Bataan).